A escola, o PNAIC e a dinamização de acervos literários - Serafini, Caticiane Belusso (2016)
The present study approaches the reading theme, the reader formation and the development of reading practices in class from the boosting of the literary collections of complimentary works, available by the National Program of Didactical books (Programa Nacional do Livro Didático PNLD) to the National Pact for literacy at the Right Age (Pacto Nacional pela Alfabetização na Idade Certa PNAIC) for the 1st to 3rd years of the elementary school. In order to do so, it aims at stimulating teachers of these grades from public municipal schools to build innovative reading practices in different languages and supports from the collections of complimentary works, helping their students to develop the taste for reading and at the same time to enhance their reading in a contemporary perspective. The work purpose is based in the legal aspects of implementation of the PNAIC in the theoretical principles of literacy of Soares (2001, 2003, 2004a, 2004b), Psychogenesis of written language developed by Ferreiro and Teberosky (1988) and conceptions of Chartier (1998, 2014a, 2014b), Silva (1991, 1998, 1999, 2009, 2012) Zilberman (2003, 2009, 2014) and Rösing (1988, 1999, 2014, 2015) on reading, reader and mediation of the teacher-reader in schools. The methodological procedure relies on the assumptions Chizzotti (1995) about the case study as qualitative research, carried out through the use of questionnaires aimed at managers, coordinators and literacy teachers in two public schools participating in the PNAIC. Reading as a social practice presupposes the formation of autonomous readers and able to understand and make sense of what one is reading, as well as establishing relationships between reading and its social and cultural environment. In this perspective, the planning and development of hyper media reading practices contribute to the formation of more critical and thoughtful readers, reading lovers in different languages and supports. Added to this, there is the importance of the teacher also being a reader of example and, from there, to get readers to mediate the formation process in the classroom more efficiently. The research findings reinforced the concern with the low rates compared to the reading and writing education in the country, pointed out the importance of the involvement of individuals with literary reading for their personal, social and cultural development and the improvement of their reading competence. They have also showed the need for the teacher to have autonomy and determination to seek other reading materials in addition to the ones at school and showed the construction of hyper media reading practices that contribute significantly to the formation of readers in different languages and supports